Gangurinn : 20 ára. - Fridjonsson, Helgi Thorgils; Thorláksson, Eirlkur; Listasafn Reykjavíkur, Hafnarhús, Reykjavík (Reykjavík : Listasafn Reykjavíkur, 2000)
Stepanek, Alice ; Maslin, Steven ; Strízek, Antonín ; Johnston, Alan ; Adlers, Bengt ; Mauro, Carlo ; Santachiara, Carlo ; van Koolwijk, Claudia ; Mo, Chung Eun ; Schifferle, Claudia ; Weiss, David ; Fischli, Peter ; et al.
Lisasafn Reykjavíkur, Hafnarhús, september - október 2000
kunstcatalogus